Зародження економічної науки на Буковині: діалектика взаємодії особистості та середовища в процесі прийняття рішень - Сторощук, Богдан Дмитрович (Чернівці–Сучава: БДМУ, 2024)
The paper analyzes the structure and methodological features of the creative achievements of Kleinwechter and Schumpeter. Тhe relationship between the scientist and his environment are analyzed both at the level of personal communication and at the level of commonality of methodology with other leading scientists of the time. Separately, the methodology for studying the behavior and socio-economic role of the entrepreneur as a «creative destroyer» is considered. In this context, the biography of Schumpeter himself, his successes and failures in the field of scientific and applied activity are also analyzed. Accordingly, a more thorough analysis of the content of the first editions of the scientist’s scientific publications, in particular, his reviews of the works of other leading scientists of that time, as well as documents reflecting various aspects of the organization of the teaching work of the outstanding scientist Joseph Alois Schumpeter, is justified as a subject of further research in this direction. The determining direction of such research is considered to be the elucidation of the regularities of the dialectical confrontation of the old with the new in both the theoretical and practical spheres, which makes new combinations more viable, more oriented towards a better satisfaction of our needs
Keywords: Friedrich Kleinwechter, Joseph Alois Schumpeter, Austrian school, historical school, neoclassical direction, creative destruction, innovation, history of economic science, non-economic criteria, neoliberalism